Spirulina supplementation and anthropometric indices: A systematic review and meta‐analysis of controlled clinical trials. (23rd September 2020) - Zarezadeh, Meysam; Faghfouri, Amir Hossein; Radkhah, Nima; Foroumandi, Elaheh; Khorshidi, Masoud; Rasouli, Ahmadreza; Zarei, Mahtab; Mohammadzadeh Honarvar, Niyaz; Hazhir Karzar, Nazanin; Ebrahimi Mamaghani, Mehrangiz
Abstract : Obesity and overweight are associated with the burden of chronic diseases. The aim of the present meta‐analysis is to determine the efficacy of spirulina in reducing of obesity indices. PubMed, Web of Science, Scopus, EMBASE and Cochrane library databases were searched up to November 2019. Randomized controlled trials comparing spirulina supplementation with a placebo or no treatment for anthropometric indices were included. Meta‐analysis was performed using random‐effects model. Subgroup analysis and meta‐regression were carried out. Publication bias was evaluated using standard methods. Spirulina had ameliorative effects on weight (WMD = −1.85 Kg; 95% CI: −2.44, −1.26; p < .001; I 2 = 82.4%, p < .001), and waist circumference (WMD = −1.09 cm; 95% CI: −2.16, −0.01; p = .046; I 2 = 0.0%, p = .757) while no significant effect was shown on body mass index, even after sensitivity analysis (SMD = −0.53 Kg/m 2 ; 95% CI: −1.25, 0.19; p = .149; I 2 = 92.9%, p < .001); however, spirulina was effective in studies lasted for at least 12 weeks (SMD = −1.25 Kg/m 2 ; 95% CI: −2.21, −0.28; p = .011; I 2 = 90.8%, p < .001). Spirulina supplementation exerts beneficial effects on weight and waist circumference. The ameliorative effect of spirulina on body mass index was revealed in longer duration of supplementation.